Online Learning Paradigm in Elementary Schools: An Evaluation by Teachers in Indonesia during The COVID-19 Pandemic - Irfan Fauzi; Herli Salim; Ulwan Syafrudin (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2021)
This research aims to explain in detail the evaluation of online learning in elementary schools during the COVID-19 pandemic in Indonesia. This research used a quantitative approach to the type of survey. The survey contains the evaluation of teachers in implementing online learning (pedagogic relations, collaboration teacher-parents, and developers and facilitators of learning access). The results of this research indicated that: 1) the teacher-student pedagogical relationship shows a good thing, although teachers experience limitations and difficulties in doing online learning, the teachers continue to carry out their professional responsibilities well by planning, implementing and evaluating their online learning activities, 2) in the context of teacher-parent collaboration, both of them are committed to collaborating in online learning, even though in practice the teacher is experiencing difficulties in communicating with parents, and 3) access to learning made and developed by teachers is fairly good, this is based on a variety of learning facilities provided such as the use of diverse applications as well as interactive media and teaching materials that help in the transfer of knowledge to students, although in learning it also sometimes experiences internet network constraints. The online learning paradigm in this research has become a new concept. So it is very important to do a detailed research. This research is expected to be an evaluation material for various parties in conducting online learning, besides this research can also facilitate other researchers to develop research on online learning, especially in elementary schools. Keywords: Online Learning, Online Learning Paradigm, Evaluation Teachers